Negative electrode active material, negative electrode, and secondary battery including same

By condensing the first silicon particles into the second silicon particles and depositing a carbon layer, the problem of physical rupture caused by volume expansion during the charging/discharging process of silicon-based negative electrode active material is solved, and the initial capacity and capacity maintenance of the secondary battery are improved , and achieves improvements in conductivity and durability.

CN119256403APending Publication Date: 2025-01-03DONGJIN SEMICHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380040956.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-16
Filing Date
2023-05-16
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing silicon-based negative electrode active materials physically rupture due to volume expansion during charging/discharging, resulting in reduced conductivity and durability, and there are problems of production difficulties and capacity loss in the synthesis of nano-scale silicon particles.

Method used

By condensing the first silicon particles into the second silicon particles and depositing a carbon layer on its surface, including free crystalline carbon and amorphous carbon, satisfying a specific differential capacity curve ratio, heat treatment is performed to restore the silicon crystals to form improved conductivity and durable negative electrode active material.

Benefits of technology

The initial capacity and capacity retention rate of the secondary battery are significantly improved, physical rupture of the silicon surface is prevented, and adhesion and durability to the electrode are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137123770000131
    Figure BDA0005137123770000131
  • Figure BDA0005137123770000151
    Figure BDA0005137123770000151
  • Figure BDA0005137123770000171
    Figure BDA0005137123770000171
Patent Text Reader

Abstract

The present invention provides a negative electrode active material having improved conductivity and durability by restoring damage to silicon crystals during secondary granulation. An embodiment of the present invention provides a negative electrode active material comprising: second silicon particles formed by aggregating first silicon particles; and a carbon layer on the second silicon particles, the carbon layer satisfying the formula 1 in a differential capacity plot of a half-cell including the negative electrode active material, the differential capacity plot of the half-cell including the negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode active material, and more particularly, to a negative electrode active material, a negative electrode, and a secondary battery including the same. Background Art

[0002] With the rapid growth of the secondary battery market, the demand for high-capacity batteries has increased dramatically, and therefore the demand for silicon-based negative electrode active materials that can theoretically achieve high capacity has also risen sharply. However, due to the physical rupture caused by volume expansion during charging / discharging and the resulting side reactions, there are limitations in achieving the performance of theoretical capacity. In order to prevent this physical rupture due to volume expansion, silicon particles with a size of about 150nm or less must be used. In the past, single crystal silicon below 150nm was produced by synthesizing nano-scale silicon. However, there is a problem of difficulty in large-scale production in the process of synthesizing nano-scale silicon. In order to solve this problem, a technology for grinding silicon minerals to a level of 150nm or less has been introduced.

[0003] However, when the primary particles are simply crushed to a particle size of 150nm or less for use, the specific surface area becomes too large, resulting in a problem of difficulty in adhering to the electrode. In order to solve this problem, a process is adopted in which a device such as a spray dryer is used to aggregate primary particles with a particle size of 150nm or less to form secondary particles. However, in the process of crushing silicon into primary particles, the silicon crystals are damaged and the crystal size is reduced, resulting in capacity loss. In addition, when secondary particles are formed, when bonding is performed between primary silicon particles without a binder, the conductivity and physical durability are greatly reduced. Summary of the invention

[0004] Problem that the invention aims to solve

[0005] An object of the present invention is to provide a negative electrode active material capable of restoring silicon crystals damaged in the process of converting silicon particles into secondary particles.

[0006] Another object of the present invention is to provide a negative electrode active material having improved conductivity and durability.

[0007] Another object of the present invention is to provide a negative electrode active material that improves the initial capacity and capacity retention rate of a secondary battery by satisfying parameters related to the amount of change in capacity with respect to voltage (dQ / dV).

[0008] Another object of the present invention is to provide a negative electrode comprising the negative electrode active material.

[0009] Another object of the present invention is to provide a secondary battery comprising the negative electrode.

[0010] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.

[0011] Solutions for solving technical problems

[0012] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a negative electrode active material is provided, which includes: second silicon particles formed by agglomerating first silicon particles; and a carbon layer located on the above-mentioned second silicon particles, and the differential capacity curve of the half-cell including the above-mentioned negative electrode active material satisfies the following formula 1.

[0013] [Formula 1]

[0014] R=(dQ 2 / dV 2 ) / (dQ 1 / dV 1 )≥1.2

[0015] In the above formula 1, dQ 1 / dV 1 is the maximum discharge peak value of the first charge / discharge cycle in the range of 0.3V to 0.6V, dQ 2 / dV 2 is the maximum discharge peak value of the second charge / discharge cycle in the range of 0.3V to 0.6V, and R is the ratio of the maximum discharge peak value.

[0016] According to a second aspect of the present invention, in the first aspect, R in Formula 1 may be 3.5 or less.

[0017] According to a third aspect of the present invention, in the first or second aspect, R in Formula 1 may be 1.5 to 2.8.

[0018] According to a fourth aspect of the present invention, in any one of the first to third aspects, the carbon layer may include one selected from the group consisting of crystalline carbon, amorphous carbon, and a combination thereof.

[0019] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the carbon layer may include the crystalline carbon derived from pitch and the amorphous carbon derived from a carbon precursor.

[0020] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, the carbon content may be 5 wt % to 80 wt % based on the total weight of the negative electrode active material.

[0021] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the carbon content may be 35 wt % to 60 wt % based on the total weight of the negative electrode active material.

[0022] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the first silicon particles may have a crystalline size of 15 nm to 30 nm.

[0023] According to a ninth aspect of the present invention, in any one of the first to eighth aspects, the crystal size of the first silicon particles may be 17 nm to 20 nm.

[0024] According to a tenth aspect of the present invention, in any one of the first to ninth aspects, the carbon layer may have a thickness of 20 nm to 80 nm.

[0025] According to an eleventh aspect of the present invention, in any one of the first to tenth aspects, the carbon layer may have a thickness of 40 nm to 80 nm.

[0026] According to a twelfth aspect of the present invention, there may be provided a negative electrode including the negative electrode active material according to any one of the first to eleventh aspects described above.

[0027] According to a thirteenth aspect of the present invention, there may be provided a secondary battery including the negative electrode according to the above-described twelfth aspect.

[0028] Effects of the Invention

[0029] According to one aspect of the present invention, a negative electrode active material having improved conductivity and physical durability while restoring silicon crystals damaged in the process of converting first silicon particles (primary particles) into secondary particles can be provided. By using these negative electrode active materials, the performance of secondary batteries can be significantly improved by increasing the initial capacity and capacity retention rate of secondary batteries.

[0030] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. DETAILED DESCRIPTION

[0031] Hereinafter, each configuration of the present invention will be described in more detail so that those skilled in the art can easily implement it, but this is only an example, and the scope of the present invention is not limited to the following contents.

[0032] In this specification, unless otherwise clearly stated, a description indicating a singular number should be understood as including the plural number.

[0033] The numerical range represented by the word "to" herein refers to the numerical range including the numerical range specified as the lower limit and the upper limit respectively before or after the word. When multiple values ​​of the upper limit or lower limit of any numerical range are mentioned, the range disclosed herein can be understood as a range with any one of the multiple upper limits mentioned as its upper limit and any one of the multiple lower limits as its lower limit.

[0034] In this specification, a "differential capacity plot" is a graph showing the relationship between charge and potential. Specifically, it is a graph obtained by measuring the change in charge as the battery potential is adjusted and then differentiating the measured charge change with respect to the potential. Generally speaking, the electrochemical characteristics of a secondary battery change during charging and discharging, and the differential capacity plot can be used to confirm the characteristics.

[0035] An embodiment of the present invention provides a negative electrode active material, which includes: second silicon particles formed by agglomerating first silicon particles; and a carbon layer located on the second silicon particles, wherein the differential capacity curve of a half-cell including the negative electrode active material satisfies the following formula 1.

[0036] [Formula 1]

[0037] R=(dQ 2 / dV 2 ) / (dQ 1 / dV 1 )≥1.2

[0038] In the above formula 1, dQ 1 / dV 1 is the maximum discharge peak value of the first charge / discharge cycle in the range of 0.3V to 0.6V, dQ 2 / dV 2 is the maximum discharge peak value of the second charge / discharge cycle in the range of 0.3V to 0.6V, and R is the ratio of the maximum discharge peak value. According to one embodiment of the present invention, by providing a negative electrode active material satisfying the parameters of the above formula 1, a negative electrode active material having improved conductivity and physical durability while restoring silicon crystals damaged in the process of converting the first silicon particles (primary particles) into secondary particles can be provided. By using these negative electrode active materials, the performance of the secondary battery can be significantly improved by increasing the initial capacity and capacity retention rate of the secondary battery.

[0039] Hereinafter, the constitution of the present invention will be described in more detail.

[0040] 1. Negative electrode active material and preparation method thereof

[0041] The negative electrode active material of the present invention includes second silicon particles formed by agglomeration of first silicon particles. The above-mentioned second silicon particles can be prepared by converting the above-mentioned first silicon particles into secondary particles. When the first silicon particles (primary particles) are used alone to manufacture electrodes without a secondary granulation process, the surface of the silicon may be physically broken during the process of lithium embedding / de-embedding silicon during charging / discharging of the secondary battery, and the adhesion to the electrode is reduced and the crystal size is reduced due to the excessively large specific surface area of ​​silicon, so the problem of not being able to fully utilize the battery capacity may occur. According to one embodiment of the present invention, by using the second silicon particles that are secondarily granulated, the physical breakage phenomenon of the silicon surface can be effectively prevented, and the decrease in adhesion to the electrode can be prevented.

[0042] Specifically, the average particle size (D50) of the first silicon particles may be 100 nm to 200 nm, more specifically, 100 nm to 150 nm. The average particle size (D50) of the second silicon particles may be 3 μm to 30 μm, specifically, 3 μm to 10 μm. When the average particle size of the second silicon particles satisfies the above numerical range, the adhesion and durability of the electrode may be improved.

[0043] The negative electrode active material according to the present invention includes a carbon layer on the above-mentioned second silicon particles. Specifically, the above-mentioned carbon layer may include one selected from the group consisting of crystalline carbon, amorphous carbon and a combination thereof, and more specifically, may include a combination of crystalline carbon and amorphous carbon. Specifically, the above-mentioned carbon layer may include crystalline carbon derived from asphalt and amorphous carbon derived from a carbon precursor. Since the above-mentioned carbon layer includes crystalline carbon and amorphous carbon, the conductivity and durability of the negative electrode active material can be improved, and the capacity and retention rate of the battery can be significantly improved.

[0044] For example, the carbon source for producing the above-mentioned crystalline carbon may be pitch such as coal tar pitch and petroleum pitch, aromatic carbon materials such as sugars, lignin and cellulose, and polyacrylonitrile, etc. Specifically, when pitch is used as the carbon source for producing the above-mentioned crystalline carbon, the carbon content remaining after heat treatment can be adjusted to a maximum of 80% by the softening point.

[0045] For example, the carbon precursor for producing the amorphous carbon may be a hydrocarbon in the form of a gas, specifically, acetylene, toluene, methane, etc. The carbon precursor may be deposited on the second silicon particles in the form of an amorphous carbon layer by chemical vapor deposition (CVD). Since the carbon precursor is continuously supplied in the form of a gas during the deposition of the carbon layer containing amorphous carbon, a pore-free carbon layer can be formed. Therefore, the generation of an excessive solid electrolyte interphase (SEI) layer can be suppressed during the charge and discharge process, while serving as a protective film to prevent the volume expansion of silicon.

[0046] The following Formula 1 may be satisfied in a differential capacity curve of a half-cell including the negative electrode active material according to the present invention.

[0047] [Formula 1]

[0048] R=(dQ 2 / dV 2 ) / (dQ 1 / dV 1 )≥1.2

[0049] dQ 1 / dV 1 is the maximum discharge peak value of the first charge / discharge cycle in the range of 0.3V to 0.6V, dQ 2 / dV 2 is the maximum discharge peak value of the second charge / discharge cycle in the range of 0.3V to 0.6V. According to one embodiment of the present invention, when relative to dQ corresponding to the two variables 1 / dV 1 dQ 2 / dV 2When the ratio satisfies the above numerical range, the damaged crystals can be effectively restored by the heat treatment temperature, so that a negative electrode active material with improved conductivity and durability can be provided. The above negative electrode active material can be heat-treated at the same time or after the second silicon particles are formed by converting the first silicon particles into secondary particles. The above negative electrode active material can be heat-treated at the same time or after the carbon layer is deposited on the second silicon particles. At least one of the above second silicon particles and the above carbon layer can be formed by a heat treatment process at 600°C to 1200°C, specifically, at 700°C to 1000°C, and more specifically, at 700°C to 900°C. If the temperature of the above heat treatment process is lower than the above numerical range, the damaged crystals may not be fully restored, and if the temperature of the above heat treatment process exceeds the above numerical range, the first silicon particles may melt, resulting in the problem of being unable to maintain the shape of the primary particles. Specifically, the negative electrode active material can be prepared by dispersing the crushed first silicon particles in a solvent, or by dispersing the crushed first silicon particles and asphalt in a solvent, and / or by introducing the secondary particles in which the carbon layer is deposited by introducing the carbon precursor in the form of a gas by chemical vapor deposition into a sintering furnace, thereby performing a heat treatment process. In one embodiment of the present invention, the relative dQ as the correlation between the two variables is obtained by performing the heat treatment process. 1 / dV 1 dQ 2 / dV 2 The optimal range of recovery of damaged silicon crystals improves the durability of the electrode.

[0050] According to another embodiment of the present invention, R in the above formula 1 may be 3.5 or less, specifically, R in the above formula 1 may be 1.5 to 2.8. In the above formula 1, when the above range of R satisfies the above numerical range, the durability of the negative electrode active material, the capacity and retention rate of the battery can be significantly improved.

[0051] Based on the total weight of the above-mentioned negative electrode active material, the carbon content according to the present invention can be 5 wt % to 80 wt %, specifically, 35 wt % to 60 wt %, more specifically, 50 wt % to 60 wt %. The above-mentioned carbon content can be measured using a conventional elemental analyzer in the relevant technical field. When the above-mentioned carbon content meets the above-mentioned numerical range, the capacity or retention rate of the battery can be improved.

[0052] According to the present invention, the crystal size of the first silicon particles can be 15nm to 30nm, specifically, 17nm to 20nm. The crystal size of the first silicon particles can be calculated by X-ray diffraction (XRD) analysis and the Scherrer-Wilson equation. When the crystal size of the first silicon particles meets the above numerical range, the capacity and capacity retention rate of the battery can be improved.

[0053] The thickness of the carbon layer of the negative electrode active material according to the present invention can be 1nm to 110nm, specifically, 10nm to 100nm, more specifically, 20nm to 80nm, and even more specifically, 40nm to 80nm. The thickness of the above-mentioned carbon layer can be measured by observing the transmission electron microscope (TEM) photo of the manufactured negative electrode active material. When the thickness of the above-mentioned carbon layer meets the above-mentioned numerical range, the capacity and capacity retention rate of the battery can be further improved.

[0054] The BET specific surface area of ​​the negative electrode active material according to the present invention can be 10 m 2 / g to 200m 2 / g, specifically, 10m 2 / g to 150m 2 / g, more specifically, 10m 2 / g to 80m 2 The specific surface area of ​​the negative electrode active material is measured using a Brunauer-Emmett-Teller (BET) analysis method and may be a result satisfying the average particle size range of the negative electrode active material.

[0055] The total pore volume of the negative electrode active material of the present invention may be 0.05 cm 3 / g to 1.0cm 3 / g, specifically 0.05cm 3 / g to 0.5cm 3 / g, more specifically 0.05cm 3 / g to 0.2cm 3 The total pore volume can be measured using a Barrett-Joyner-Halenda (BJH) analysis method.

[0056] Yet another embodiment of the present invention may provide a method for preparing a negative electrode active material.

[0057] The method for preparing a negative electrode active material according to one embodiment of the present invention includes: a step (S1) of preparing a dispersion containing first silicon particles; and a step (S2) of spraying the dispersion to prepare second silicon particles. The dispersion may further contain pitch as needed. Based on 100 parts by weight of the first silicon particles, the content of the pitch may be greater than 0 and less than 50 parts by weight, specifically, 20 parts by weight to 40 parts by weight. If the content of the pitch is less than the above numerical range, a carbon layer containing sufficient crystalline carbon may not be formed. If it exceeds the above numerical range, the number of pores contained in the negative electrode active material may be too large.

[0058] The method for preparing a negative electrode active material according to another embodiment of the present invention may further include introducing the above-mentioned second silicon particles into a sintering furnace and performing a heat treatment step (S3) at a temperature below 600°C to 1200°C in a carbon precursor (gas) atmosphere. Through the above-mentioned step (S3), the carbon layer can be realized in a state where crystalline carbon and amorphous carbon are mixed, so that the conductivity and durability can be improved at the same time. Therefore, the capacity and retention rate of the battery can be significantly improved.

[0059] The thickness and carbon content of the carbon layer can be appropriately adjusted according to the content of the pitch or the content of the carbon precursor (gas).

[0060] According to another embodiment of the present invention, the negative electrode active material may further include one or more other negative electrode active materials such as carbon-based negative electrode active materials, silicon-based negative electrode active materials and tin-based negative electrode active materials in addition to the silicon-carbon composite negative electrode active material. For example, the above-mentioned other negative electrode active materials may be graphite such as natural graphite, artificial graphite, hard carbon, soft carbon, silicon, silicon alloy, silicon oxide, tin, tin alloy, tin oxide or silicon-tin alloy. The above-mentioned other negative electrode active materials may be mixed with the above-mentioned second silicon particles to form negative electrode active materials. In this case, for example, the content of the silicon-carbon composite negative electrode active material according to the present invention may be 0.5% by weight to 30% by weight based on the weight of the solid matter of the total negative electrode active material including the silicon-carbon composite negative electrode active material and other negative electrode active materials, specifically, it may be 5% by weight to 15% by weight.

[0061] 2. Negative electrode

[0062] Still another embodiment of the present invention may provide a negative electrode slurry and a negative electrode including the negative electrode active material.

[0063] The content of the negative electrode active material according to one embodiment of the present invention may be 60% to 80% by weight based on the weight of the total solids of the negative electrode slurry. When the negative electrode active material according to another embodiment of the present invention further comprises other negative electrode active materials, the content of the negative electrode active material may be 90% to 99% by weight, specifically, 95% to 99% by weight, based on the total solids weight of the negative electrode slurry. When the content of the negative electrode active material satisfies the above numerical range, a high-capacity or high-output battery can be realized by effectively storing or releasing lithium ions from the positive electrode.

[0064] The negative electrode slurry according to the present invention may further include a conductive material, a binder, and a solvent.

[0065] As the above-mentioned conductive material, there is no particular limitation as long as it is a material that has conductivity and does not cause chemical changes in the battery. As the above-mentioned conductive material, for example, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc., carbon black, thermal black, etc., conductive fibers such as carbon fibers or metal fibers, carbon nanotubes, fluorocarbons, metal powders such as aluminum powder, nickel powder, etc., conductive whiskers such as zinc oxide, potassium titanate, etc., conductive metal oxides such as titanium oxide, etc., polyphenylene derivatives, etc., or one or more conductive materials can be used. For example, based on the total solid weight of the negative electrode slurry, the content of the above-mentioned conductive material can be 0.01 wt% to 20 wt%.

[0066] The binder is a component that helps to bind the conductive material, the negative electrode active material or the current collector, and generally, its content can be 0.1 wt % to 20 wt % based on the total solid weight of the anode slurry. For example, the binder can be one or a mixture of two or more of the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HEP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, styrene butadiene rubber, nitrile butadiene rubber and lithium-substituted polyacrylate (lithium polyacrylate, Li-PAA).

[0067] For example, the solvent may include water or an organic solvent such as N-methyl-2-pyrrolidone (NMP).

[0068] The negative electrode slurry according to the present invention may further contain additives such as a dispersant, etc., as necessary.

[0069] The negative electrode according to the present invention may be prepared by coating the above-mentioned negative electrode slurry on at least one side of a current collector, followed by drying and calendering processes.

[0070] As the negative electrode current collector, there is no particular limitation as long as it does not induce chemical changes in the battery and has conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. The thickness of the current collector is not particularly limited, but can be in the common range of 3 μm to 500 μm.

[0071] 3. Secondary battery

[0072] Another embodiment of the present invention may provide a secondary battery including the negative electrode. The description repeated with the above parts will be briefly described or omitted.

[0073] The secondary battery according to the present invention further includes a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte provided for ion movement between the negative electrode and the positive electrode.

[0074] The above-mentioned positive electrode can be prepared by mixing the positive electrode active material, conductive material, binder and solvent to prepare the positive electrode slurry and then directly coating it on the current collector, or casting it on a separate support and peeling it off from the support to obtain a positive electrode active material film, and then laminating the film on the metal current collector.

[0075] For example, the positive electrode active material may be selected from the group consisting of LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiFePO4, Li[NiCoMn]O2 and LiNi 1-x-y-z Co x M1 y M2 z The above M1 and M2 are each independently selected from the group consisting of Al, Ni, Co, Fe, Mn, V, Cr, Ti, W, Ta, Mg and Mo, and x, y and z are each independently the atomic fraction of the oxide constituent element, and may satisfy 0≤x<0.5, 0≤y<0.5, 0≤z<0.5, 0≤ <x+y+z<1。

[0076] As the above-mentioned separator, a conventional porous polymer film can be used. For example, a porous polymer film prepared from polyolefin polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer can be used alone or in a stack. In addition, a thin insulating film with high ion permeability and mechanical strength can be used. The above-mentioned separator can include a safety reinforced separator (SRS) whose surface is thinly coated with a ceramic material. In addition, as the above-mentioned separator, a conventional porous non-woven fabric can be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc., but is not limited thereto.

[0077] The electrolyte solution may include a lithium salt as an electrolyte and an organic solvent for dissolving the lithium salt. As the lithium salt, any electrolyte solution generally used for secondary batteries may be used without limitation.

[0078] As the organic solvent contained in the above-mentioned electrolyte, the organic solvent commonly used in the electrolyte for lithium secondary batteries can be used without restriction. As the above-mentioned organic solvent, for example, one or a mixture of two or more selected from the group consisting of propylene carbonate (propylene carbonate, PC), ethylene carbonate (ethylene carbonate, EC), diethyl carbonate (diethyl carbonate, DEC), dimethyl carbonate (dimethyl carbonate, DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, dipropyl carbonate, dimethyl sulfite, acetonitrile, dimethoxyethane, diethoxyethane, ethylene carbonate, cyclopentane sulfone, γ-butyrolactone, propylene sulfoxide and tetrahydrofuran can be used.

[0079] Hereinafter, an embodiment of the present invention will be described in more detail so that those skilled in the art can easily implement it, but this is only an example, and the scope of the present invention is not limited to the following contents.

[0080] [Preparation Example 1: Preparation of negative electrode active material]

[0081] <Example 1 to Example 4: Carbon layer using asphalt as raw material>

[0082] 1.1 Preparation of secondary particles

[0083] The ground first silicon particles (D50: 120nm) and pitch powder (Pitch powder) are dispersed in ethanol, and the dispersion is sprayed through a spray dryer to prepare second silicon particles (secondary particles). The content of the ground first silicon particles is adjusted to 3% by weight based on the total weight of the dispersion. The nozzle-type spray dryer is used, and a pressure (100 Torr) sufficient to uniformly spray droplets is applied by an inert gas (Ar), and the outlet temperature of the spray dryer is set to 85°C, thereby preparing second silicon particles (secondary particles) with an average size (D50) of 5μm.

[0084] 1.2 Heat treatment process

[0085] The above-mentioned second silicon particles (secondary particles) were put into a sintering furnace and subjected to a heat treatment process under the heat treatment temperature conditions according to the following Table 1 to prepare a negative electrode active material stacked with a final carbon layer.

[0086] <Examples 5 to 9: Carbon Layer Using aC as Raw Material>

[0087] The ground first silicon particles (D50: 120nm) are dispersed in ethanol, and then the dispersion is sprayed by a spray dryer to prepare second silicon particles (secondary particles). The content of the ground first silicon particles is adjusted to 3% by weight based on the total weight of the dispersion. Using the nozzle-type spray dryer, a pressure (100 Torr) sufficient to spray droplets evenly is applied by an inert gas (Ar), and the outlet temperature of the spray dryer is set to 85°C, thereby preparing a second silicon particle (secondary particle) with an average size (D50) of 5 μm. Then, in the above-mentioned heat treatment process, acetylene gas is additionally added according to the chemical vapor deposition process to prepare the final negative electrode active material.

[0088] <Example 10 to Example 21: Carbon layer using asphalt + aC as raw material>

[0089] The negative electrode active material was prepared in the same manner as in Examples 1 to 4 except that acetylene gas was additionally added in the above heat treatment process according to the chemical vapor deposition process to prepare the final negative electrode active material.

[0090] <Comparative Example 1: Negative electrode active material without heat treatment process>

[0091] A negative electrode active material was prepared in the same manner as in Examples 5 to 9 except that the above-mentioned heat treatment process and chemical vapor deposition process were omitted and the crystal size of the first silicon particles was adjusted to the crystal size shown in Table 1 below.

[0092] <Comparative Example 2: Heat Treatment Process Temperature of 400°C>

[0093] A negative electrode active material was prepared in the same manner as in Comparative Example 1 except that the crystal size of the first silicon particles was adjusted to the crystal size shown in Table 1 below and the second silicon particles were placed in a sintering furnace to undergo a heat treatment process at 400°C.

[0094] <Comparative Example 3: Heat Treatment Process Temperature of 600°C>

[0095] A negative electrode active material was prepared in the same manner as in Comparative Example 1 except that the crystal size of the first silicon particles was adjusted to the crystal size shown in Table 1 below and the second silicon particles were placed in a sintering furnace to undergo a heat treatment process at 600°C.

[0096] Table 1

[0097]

[0098] [Preparation Example 2: Preparation of half-cell]

[0099] Preparation of negative electrode

[0100] Graphite prepared in the above-mentioned Preparation Example 1: Negative electrode active material: A negative electrode slurry (total solid content: 50 wt %) was prepared by mixing carboxymethylcellulose (CMC): styrene-butadiene rubber (SBR) in a weight ratio of 87:10:1.5:1.5 and dispersing in water. Subsequently, the above-mentioned negative electrode slurry was coated on one side of a copper foil (thickness: 18 μm) as a current collector, and then dried at 90° C. for 180 minutes to prepare a negative electrode with a total thickness of 90 μm.

[0101] Preparation of half-cell

[0102] The prepared negative electrode, counter electrode (lithium metal) and a polyethylene separator between the negative electrode and the counter electrode were placed in a battery case, and an electrolyte (containing 1M LiPF6) mixed with fluoroethylene carbonate (FEC) and dimethyl carbonate (DMC) in a volume ratio of 3:7 was injected to prepare a half-cell injected with the electrolyte.

[0103] [Experimental Example 2: Performance Evaluation of Half-Cell]

[0104] The performance of the half-cell according to the above Preparation Example 2 was evaluated by the following measurement method using WBCS3000 measurement equipment from WonATech.

[0105] 1) R (discharge peak ratio)

[0106] In order to evaluate the stable charge / discharge performance of the half-cell according to the above-mentioned Preparation Example 2, the evaluation was performed at a current of 0.1C, and the charge amount and voltage value during charging and discharging were used to plot a dQ / dV curve relative to voltage, wherein the y-axis is the capacity change (dQ / dV) relative to voltage, the x-axis is the voltage, and the dQ / dV discharge peak ratio value near 0.5V is shown in Table 2 below.

[0107] 2) First cycle capacity

[0108] After the initial stabilization step, when the half-cell according to Preparation Example 2 was evaluated at a current level of 0.5C, the initial capacity was measured and is shown in Table 2 below.

[0109] 3) Retention rate evaluation (100 cycle retention rate)

[0110] After the initial stabilization step, the half cell according to the above Preparation Example 2 was charged / discharged 100 times at a current level of 0.5C, and the ratio (%) of discharge capacity / initial capacity was measured. The results are shown in Table 2 below.

[0111] Table 2

[0112]

[0113] When comparing Examples 1 to 4 in Table 2 above, it can be confirmed that both the initial capacity and the retention rate tend to increase with the increase in carbon content, and according to the asphalt content, R = (dQ 2 / dV 2 ) / (dQ 1 / dV 1 This can be speculated to be caused by the interaction with silicon crystals during the asphalt crystallization process.

[0114] When comparing Examples 5 to 9 in the above Table 2, it can be confirmed that the initial capacity and retention rate tend to increase with the increase in carbon content, similarly to Examples 1 to 4. However, compared with asphalt, it can be confirmed that the thickness of the outer carbon layer is greater at the same carbon content, which indicates that a part of the asphalt cannot be crystallized and is lost during the crystallization process, resulting in pores, while in the process of depositing the amorphous carbon layer, acetylene gas is continuously supplied, so there is no factor causing pores.

[0115] When comparing Examples 10 to 15 in Table 2 above, it can be confirmed that R tends to increase as the crystal size of the first silicon particles increases. However, it can be confirmed that when the crystal size of the first silicon particles is too large, a-SiLi is excessively generated. δ, resulting in a decrease in capacity and retention rate. Therefore, it can be confirmed that when the crystal size of the first silicon particles (primary particles) is 15nm to 30nm, specifically 17nm to 20nm, the capacity of the battery increases.

[0116] When comparing Examples 16 to 21 in which asphalt and acetylene gas are used as carbon sources at the same time in Table 2 above, it can be confirmed that the thickness of the carbon layer is greatly reduced compared to the carbon content. In addition, when the thickness of the carbon layer of Example 17 is about 60nm, the best capacity and retention rate are shown. If the carbon layer is over-laminated beyond this thickness, the amount of silicon that can accept lithium is reduced, and there is a tendency for the capacity and retention rate to decrease. In addition, it can be confirmed that when the thickness of the carbon layer exceeds 80nm and the carbon layer is stacked to 110nm, the capacity and retention rate are reduced compared to the case where an amorphous carbon layer is stacked alone. When preparing a composite using two carbon sources to stack carbon layers, it can be confirmed that the thickness of the carbon layer is preferably 20nm to 80nm, and most preferably 40nm to 80nm.

[0117] When comparing Comparative Examples 1 to 3 in the above Table 2, it can be confirmed that the results of adjusting the crystal size of the first silicon particles (primary particles) by heat treatment without adding a carbon layer show that the capacity and retention rate are improved compared with Comparative Example 1 which has not been heat treated, and the increased crystal size is reflected in the R value.

[0118] With reference to the comparative examples and examples in Table 2 above, it can be confirmed that in order to restore the crystal size of the crushed silicon particles and exert their proper capacity, the R value should be 1.2 or more.

[0119] [Preparation Example 3: Preparation of a full cell]

[0120] Preparation of positive electrode

[0121] After adding a mixture of NCM (Li[NiCoMn]O2): carbon black: nitrile-butadiene rubber (NBR) in a weight ratio of 96:2:2 into a solvent (N-methylpyrrolidone), a positive electrode slurry with a total solid content of 75% by weight was prepared. The above positive electrode slurry was coated on one side of an aluminum foil (thickness: 20 μm) and then dried at 120°C for 120 minutes to obtain a positive electrode with a total thickness of 70 μm.

[0122] Preparation of full battery

[0123] Except for using the prepared positive electrode to replace the counter electrode (Li metal) to prepare a full battery, the rest was prepared in the same manner as in the above-mentioned Preparation Example 2. In this process, the unit area capacity ratio (N / P ratio) of the negative electrode to the positive electrode was adjusted to 1.1, and the positive electrode and the negative electrode were punched into 14pi and 16pi, respectively, in a 2032 button cell.

[0124] [Experimental Example 3: Performance evaluation of full battery]

[0125] For the full battery according to the above Preparation Example 3, the charging voltage was set to 4.2 V, the discharging voltage was set to 2.8 V, and the retention rate was evaluated at a current level of 0.5 C according to the same measurement method as the above Experimental Example 2.

[0126] Table 3

[0127]

[0128] Referring to Table 3 above, it can be confirmed that the capacity and retention rate of the full battery are significantly improved by heat treating the second silicon particles stacked with a carbon layer, and the full battery performance of Example 17 stacked with a carbon layer mixed with crystalline carbon and amorphous carbon using two carbon sources including pitch and acetylene gas is the most superior. It can be confirmed that in order to ensure conductivity and durability in the full battery, the capacity and retention rate of the battery are further improved when silicon particles stacked with a mixed carbon layer of crystalline carbon and amorphous carbon are used.

[0129] The preferred embodiments of the present invention are described in detail above, but the scope of the present invention is not limited thereto. Various modifications and improvements by ordinary technicians in the technical field of the present invention using the basic concepts of the present invention defined in the scope of protection of the attached invention claims also fall within the scope of the present invention.

Claims

1. A negative electrode active material, characterized in that: include: second silicon particles formed by agglomerating the first silicon particles; and a carbon layer disposed on the second silicon particle, The differential capacity curve of the half-cell including the above negative electrode active material satisfies the following formula 1: [Formula 1] R=(dQ 2 / dV 2 ) / (dQ 1 / dV 1 )≥1.2 In the above formula 1, dQ 1 / dV 1 is the maximum discharge peak value of the first charge / discharge cycle in the range of 0.3V to 0.6V, dQ 2 / dV 2 is the maximum discharge peak value of the second charge / discharge cycle in the range of 0.3V to 0.6V, R is the ratio of the maximum discharge peak.

2. The negative electrode active material according to claim 1, characterized in that In the above formula 1, R is 3.5 or less.

3. The negative electrode active material according to claim 2, characterized in that: In the above Formula 1, R is 1.5 to 2.

8.

4. The negative electrode active material according to claim 1, characterized in that The carbon layer includes one selected from the group consisting of crystalline carbon, amorphous carbon and a combination thereof.

5. The negative electrode active material according to claim 4, characterized in that The carbon layer includes the crystalline carbon derived from the pitch and the amorphous carbon derived from the carbon precursor.

6. The negative electrode active material according to claim 1, characterized in that The carbon content is 5 wt % to 80 wt % based on the total weight of the negative electrode active material.

7. The negative electrode active material according to claim 6, characterized in that: The carbon content is 35 wt % to 60 wt % based on the total weight of the negative electrode active material.

8. The negative electrode active material according to claim 1, characterized in that The crystal size of the first silicon particles is 15 nm to 30 nm.

9. The negative electrode active material according to claim 8, characterized in that The crystal size of the first silicon particles is 17 nm to 20 nm.

10. The negative electrode active material according to claim 1, characterized in that The thickness of the carbon layer is 20 nm to 80 nm.

11. The negative electrode active material according to claim 10, characterized in that: The thickness of the carbon layer is 40nm to 80nm.

12. A negative electrode, characterized in that: The negative electrode active material according to any one of claims 1 to 11 is included.

13. A secondary battery, characterized in that: The negative electrode according to claim 12 is included.